Considerations in Surgical Management of Pediatric Obstructive Sleep Apnea: Tonsillectomy and Beyond - T. C. Uwiera (Children, 2021)
Obstructive sleep apnea (OSA) is an increasingly recognized disorder with a reported incidence of 5.7% in children. Tonsillectomy (with or without adenoidectomy) in pediatric OSA in otherwise healthy non-obese children has a success rate of approximately 75%. However, the cure rate reported for all children undergoing tonsillectomy varies from 51% to 83%. This article reviews the history of tonsillectomy, its indications, techniques, various methods, risks, and successes. The article also explores other surgical options in children with residual OSA post-tonsillectomy.